Panorama of the teaching and learning of the evaluation of social policy in Mexico (2012-2018) (Revista de Investigaciones Universidad del Quindío, 2021)
The research analyzed the external evaluations of social policy in Mexico, during the period 2012-2018, with the objective to identify three types of policy learning: instrumental, social, and tactical. The analysis consisted of reviewing the following documents: the Annual Evaluation Program (PAE), the final reports of the evaluations, and the aspects susceptible to the improvement of each evaluation, considering only the evaluations with complete information in their reports. The results indicate a decrease in the total number of evaluations during this period, where 146 design evaluations were carried out, none of the indicators and 5 of the impact which was the most expensive. Of all the stakeholders responsible for conducting external design evaluations, higher education institutions stand out. Instrumental learning is the main type because all the evaluation methodologies are focused on feasibility and the means of action to achieve effectiveness. The conclusion is that evaluation methodologies proposed by CONEVAL are related to the phases of public policies because they represent incremental learning processes that must be supported by systematic evaluation exercises, but they fail to achieve the full evaluation process.
Keywords: evaluation; public policies; policy learning; methodology